FORMATION OF PSYCHOLOGICAL COMPETENCY OF AVIAFACTIVERS IN CONDITIONS OF INFLUENCE - Демченко, Н. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
This article deals with the peculiarities of the formation of psychological competence of aviation specialists in conditions of continuing education. It is indicated in the importance of forming the psychological competence of the aviation specialist, which is a system integral entity that manifests itself at different levels of the psychological reality of a person, in the internal plan - in self-regulation, and in the external plan - in activity and interaction and can be realized in conditions of continuous education, which is a priority the branch of educational systems of developed countries, noting that the continuity of education is a strategic reference point for the development of society. It is proved that psychological competence contributes to an adequate assessment of their own abilities, abilities, levels of aspirations, psychological peculiarities; selecting the most effective behavioral options in a particular situation; regulating their own emotional states, overcoming critical life situations. With regard to the factors and limitations of improving their own psychological competence, 43.4% of respondents of aviation specialists noted the absence of obstacles to improving their own psychological competence. Other factors hindering the development of competence were mostly external: overloaded with functional responsibilities (56.6%), lack of professional psychological training (39.6%), state of health (28.3%), lack of positions a psychologist in the organization (23,9%), a time limit (20,1%).